the Implant Overloading Considerations for Implant Assisted Overdentures .: (IAOD) - A El Maroush , Mohamed; M Esayah, Suleiman; Mohammed Askar, Osama (International Journal of Scientific Research and Management (IJSRM), 2021)
The loss of retention and stability are considered the most common prosthetic problems that face prosthodontics in complete denture patients especially with continued residual ridge resorption, which increased the number of patients’ seeking improvement of the retention and stability in order to use their dentures. The implant supported overdenture is considered the best option of treatment to solve these problems. Implants may be subjected to occlusal overloading during function which will negatively affect the prognosis of implant osseintegration. This encouraged us to review the literature concerning the factors affecting implant assisted overdentures (IAOD) overloading and how to control them to the benefit and comfort of the patient as well as longevity of the prosthetic.